2018
DOI: 10.4014/jmb.1808.08058
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus Methyltransferase Inhibits Type I Interferon Induction by Targeting RIG-I

Abstract: The type I interferons (IFNs) play a vital role in activation of innate immunity in response to viral infection. Accordingly, viruses have evolved to employ various survival strategies to evade innate immune responses induced by type I IFNs. For example, hepatitis E virus (HEV) encoded papain-like cysteine protease (PCP) has been shown to inhibit IFN activation signaling by suppressing K63-linked de-ubiquitination of retinoic acid-inducible gene I (RIG-I) and TANK-binding kinase 1 (TBK1), thus effectively inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 89 publications
0
49
0
Order By: Relevance
“…Type I IFN responses are a first line of defense against invading viruses Myoung, 2017a, 2017b;Kang et al, 2018;Kim and Myoung, 2018;Banerjee et al, 2019). There are 16 different type I IFN's that are known to be expressed in humans (Kindler et al, 2016): IFN-α (13 subtypes), IFN-β, IFN-κ, and IFN-ω (1 type each).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type I IFN responses are a first line of defense against invading viruses Myoung, 2017a, 2017b;Kang et al, 2018;Kim and Myoung, 2018;Banerjee et al, 2019). There are 16 different type I IFN's that are known to be expressed in humans (Kindler et al, 2016): IFN-α (13 subtypes), IFN-β, IFN-κ, and IFN-ω (1 type each).…”
Section: Discussionmentioning
confidence: 99%
“…HEK293T cells (4 × 10 5 cells/well) were seeded in a 6-well plate a day before transfection as previously described (Kang et al, 2018;Kim and Myoung, 2018;Park et al, 2019). Briefly, mixtures, containing 500 ng of Interferon (IFN)-β-luc, 100 ng of β-gal expressing plasmid as the internal control, 500 ng of immune gene stimulating plasmid and 1,000 ng of MERS accessary gene encoding or empty plasmid, were transfected using PEI transfection reagent as ratio of 1:2 (DNA: PEI) in 200 μl of opti-MEM (Thermo Fisher Scientific).…”
Section: Transfection and Luciferase Reporter Assaymentioning
confidence: 99%
“…Previously, we showed that HEV-encoded methyltransferase (MeT) strongly inhibits MDA5-mediated induction of the IFN-β promoter (Myoung and Min, 2019) as well as that of RIG-I (Kang et al, 2018). Here, we demonstrated that MeT efficiently down-regulates the phosphorylation of IRF3 S396.…”
Section: Introductionmentioning
confidence: 83%
“…Hepatitis E virus (HEV) is a single-stranded positive-sense RNA virus which is found enveloped in blood and non-enveloped in bile and feces (Denner, 2019). Its genome is known to have 3-4 partially overlapping open reading frames (ORFs): ORF1 encodes 6 non-structural proteins (Koonin et al, 1992;Ropp et al, 2000;Ahola and Karlin, 2015;Kanade et al, 2018;Kang et al, 2018) while ORF2 and ORF3 encode viral capsid protein and an ion channel, respectively (Ding et al, 2017;Kang and Myoung, 2017a;Kang et al, 2018). Recently, ORF4 has been proposed and Nair et al (2016) reported that it is expressed under certain conditions, such as ER stress, whose expression seems to be limited to HEV genotype 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation